2017
DOI: 10.5144/0256-4947.2017.114
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of overweight/obesity in high school adolescents in Jeddah and the association of obesity association with dental caries

Abstract: BACKGROUNDThe prevalence of overweight/obesity in children in Saudi Arabia is among the highest in the world. The prevalence of dental caries is also high in Saudi children. Studies on the relationship between caries and obesity in Saudi adolescents are lacking.OBJECTIVESTo study the prevalence of overweight/obesity in adolescents, and determine any association between obesity and caries.DESIGNAn analytical cross-sectional study.SETTINGPrivate and public schools in Jeddah.PATIENTS AND METHODSThe study sample c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 33 publications
7
26
1
Order By: Relevance
“…The findings of this study showed that overweight/obesity was not correlated to dental caries, which was in agreement with a number of studies,[ 28 29 30 31 32 33 ] although conflicting results are presented in various studies. Some studies have found positive relation,[ 13 15 ] whereas other studies have shown negative relation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of this study showed that overweight/obesity was not correlated to dental caries, which was in agreement with a number of studies,[ 28 29 30 31 32 33 ] although conflicting results are presented in various studies. Some studies have found positive relation,[ 13 15 ] whereas other studies have shown negative relation.…”
Section: Discussionsupporting
confidence: 93%
“…It showed a weak positive correlation between DMFT and BMI and statistical significance could be due to large sample size. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…4 Studies investigating the association between overweight/obesity and dental caries in children and adolescents have shown inconsistent results. Whereas most cross-sectional studies have shown a lack of association between obesity and dental caries, 4,5,6 a direct 7,8,9 and even an inverse association have been reported. 10,11,12 Regarding the impact of obesity on the incidence of dental caries, a systematic review of longitudinal studies by Li et al 13 showed conflicting evidence.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, several studies failed to demonstrate a significant relationship between childhood obesity and dental caries. 13 15 Given the current debate, this study, therefore, aimed to assess the relationship between teeth status represented by decayed, missed, filled teeth index (DMFT), and BMI among healthy adults.…”
mentioning
confidence: 99%